2022
DOI: 10.1111/fcp.12796
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide promoted functional recovery following sciatic nerve injury in male Wistar rats

Abstract: The impact of peripheral nerve damage on a patient's quality of life is severe. The most frequent peripheral nerve crush damage is a sciatic nerve injury. Previous research has shown that glibenclamide (GB) has neuroprotective properties in a variety of oxidative stress‐related disorders, including Alzheimer and Parkinson. The goal of this study was to see how GB affected nerve regeneration and improved function of the sciatic nerve in a rat model following a crush injury. We evaluated motor function, sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Prior investigations have documented the beneficial effects of glibenclamide in various neurodegeneration models, particularly in terms of its ultimate effects on neurons. Several studies have reported an anti-inflammatory effect of glibenclamide in connection with Parkinson’s disease (Abdelkader et al 2020 ; Qiu et al 2021 ; Ferdowsi et al 2022 ). All documented anti-inflammatory effects of glibenclamide are rooted in animal models, highlighting its ultimate impact on neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations have documented the beneficial effects of glibenclamide in various neurodegeneration models, particularly in terms of its ultimate effects on neurons. Several studies have reported an anti-inflammatory effect of glibenclamide in connection with Parkinson’s disease (Abdelkader et al 2020 ; Qiu et al 2021 ; Ferdowsi et al 2022 ). All documented anti-inflammatory effects of glibenclamide are rooted in animal models, highlighting its ultimate impact on neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Sciatic nerve injury (SNI) has the characteristics of high disability rate and di cult recovery of nerve function [1], and secondary lesions will spread to the surrounding normal tissues, resulting in chronic loss of function [2]. The etiology of secondary damage in SNI is not yet clear, but microcirculation disturbance is considered to be one of the important reasons for secondary damage [3][4][5]. Tetramethylpyrazine (TMP) can inhibit platelet aggregation, prevent thrombosis, dilate arterioles, enhance myocardial contraction, inhibit apoptosis, and reduce in ammatory reactions [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%